Bridging cultures: Innovative adaptation strategies of Indonesian students navigating academic and social challenges in the United States - Octavina, Cindy; Khairunnisa, Fathia; Lestari, Tri Puja; Silvhiany, Sary; Mirizon, Soni; Ernalida, Ernalida; Purnomo, Mulyadi Eko (Universitas Islam Sultan Agung, 2025)
This study investigated the experiences of Indonesian students pursuing higher education in the United States, highlighting the importance of understanding their cultural adaptation, academic challenges, and social integration. Despite the significant presence of Indonesian students, comprehensive research addressing their unique experiences, and challenges in a new educational environment is limited. The study aims to understand their cultural adaptation, identify academic challenges, and examine strategies for social integration. A phenomenological qualitative approach was employed, utilizing semi-structured interviews with doctoral students to gather in-depth insights. Thematic analysis reveals that cultural adaptation is significantly influenced by language barriers, differing educational norms, and social dynamics. Participants reported academic challenges related to adjusting to critical thinking-based learning and independent study practices. Additionally, social integration is often complicated by cultural misunderstandings and the individualistic values prevalent in American society. To address these challenges, students employ strategies such as building support networks, engaging in campus activities, and utilizing institutional resources. This study underscores the necessity for proactive cultural engagement and institutional support to enhance international students' experiences and foster more inclusive educational environments.